2017
DOI: 10.1007/s11120-017-0398-3
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid-to-bacteriochlorophyll energy transfer through vibronic coupling in LH2 from Phaeosprillum molischianum

Abstract: The peripheral light-harvesting antenna complex (LH2) of purple photosynthetic bacteria is an ideal testing ground for models of structure–function relationships due to its well-determined molecular structure and ultrafast energy deactivation. It has been the target for numerous studies in both theory and ultrafast spectroscopy; nevertheless, certain aspects of the convoluted relaxation network of LH2 lack a satisfactory explanation by conventional theories. For example, the initial carotenoid-to-bacteriochlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…However, they occur in a spectral region not predicted by the displaced harmonic oscillator model 40 for these modes, suggesting the presence of more complex mechanisms. It has been recently suggested that vibrational modes of accessory pigments could work as a sink, absorbing the excess energy released by energy transfer due to the mismatch of donor and acceptor levels 41 , 42 . In the case of PCP, the strongly beating signal in the upper-left portion of the maps would represent the deposition into the Per vibrational modes of the excess energy released after the S 2 → Q y transfer.…”
Section: Resultsmentioning
confidence: 99%
“…However, they occur in a spectral region not predicted by the displaced harmonic oscillator model 40 for these modes, suggesting the presence of more complex mechanisms. It has been recently suggested that vibrational modes of accessory pigments could work as a sink, absorbing the excess energy released by energy transfer due to the mismatch of donor and acceptor levels 41 , 42 . In the case of PCP, the strongly beating signal in the upper-left portion of the maps would represent the deposition into the Per vibrational modes of the excess energy released after the S 2 → Q y transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Vibronically mediated transfers are suggested to enhance the rates of electronic relaxations [4], in addition, vibronic coupling may speed up the charge separation process in reaction centers [33,34]. This phenomenon was also suggested to explain the ultrafast carotenoid to chlorophyll energy transfer in the LH2 complex [35]. Better understanding of vibronic coupling, both qualitative and quantitative is very challenging, nevertheless it might prove necessary for explaining efficient and robust primary photosynthetic phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…In Fig.2(a) and (b), we first consider the case that each site is strongly coupled to an underdamped mode with frequency 1500 cm −1 , Huang-Rhys factor s 1 = 0.5, and γ 1 = (1 ps) −1 . Such a large Huang-Rhys factor can be found in polymer-based materials in organic photovoltaics [3, 46-48, 50, 51] and photosynthetic complexes containing carotenoids [52], where vibrational progressions are well pronounced in optical responses. In addition to the underdamped modes, we couple an overdamped mode to each site, and all the modes are coupled to thermal reservoirs at room temperature.…”
mentioning
confidence: 99%